2013
DOI: 10.1002/cphc.201300447
|View full text |Cite
|
Sign up to set email alerts
|

Superfluorescent Squaraine with Efficient Two‐Photon Absorption and High Photostability

Abstract: The synthesis, linear photophysical, two-photon absorption (2PA), femtosecond transient absorption, and superfluorescence properties of a new symmetrical squaraine derivative (1) are reported. Steady-state linear spectral and photochemical properties, fluorescence lifetimes, and excitation anisotropy of 1 were investigated in various organic solvents. High fluorescence quantum yields (≈0.7) and very high photostability (photodecomposition quantum yields ≈10(-6)-10(-8)) were observed. An open-aperture Z-scan me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(86 citation statements)
references
References 81 publications
6
79
1
Order By: Relevance
“…Relatively weak 2PA efficiency (δ 2PA ∼ 100 GM) was observed in this spectral range with a noticeable increase to ∼1000 GM (long wavelength 2PA maximum) at the vibrational shoulder of the 1PA contour (at ≈600 nm). This is evidence of vibronic coupling with asymmetrical vibration modes, 11,21,71 which violates the selection rules. 72,73 The most intense short wavelength 2PA maximum with δ 2PA ≈ 8000 GM (at ≈820 nm) corresponded to the spectral range of the lowest 1PA (see insert in Figure 3a) and two-photon allowed S 0 →S n transitions (S 0 and S n are the ground and high excited electronic states of 1, respectively).…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Relatively weak 2PA efficiency (δ 2PA ∼ 100 GM) was observed in this spectral range with a noticeable increase to ∼1000 GM (long wavelength 2PA maximum) at the vibrational shoulder of the 1PA contour (at ≈600 nm). This is evidence of vibronic coupling with asymmetrical vibration modes, 11,21,71 which violates the selection rules. 72,73 The most intense short wavelength 2PA maximum with δ 2PA ≈ 8000 GM (at ≈820 nm) corresponded to the spectral range of the lowest 1PA (see insert in Figure 3a) and two-photon allowed S 0 →S n transitions (S 0 and S n are the ground and high excited electronic states of 1, respectively).…”
Section: Methodsmentioning
confidence: 87%
“…Table 1. The steady-state 1PA spectra of 1 were similar to corresponding centrosymmetric short squaraines, 11,56 and exhibited relatively narrow and sharp absorption contours (Figure 2a−c, curve 1), except for ACN where an additional H-aggregate absorbance 28 was observed at ≈606 nm ( Figure 2d, curve 1) due to low solubility. In TOL, THF, and DCM solutions no aggregation effects were observed in the concentration range C ≤ 10 −3 M (see, e.g., Figure 3a, curves 1 and 2).…”
Section: Methodsmentioning
confidence: 89%
“…We have found that the subtle changes of the number or position of the substituents close to the squaraine core influenced the twisting angle of the structure and led to significant variations in optical properties. [8b] Because of the twisted molecular structure and lower conjugation efficiency related to the intermolecular charge transfer interactions, it was reasonable to expect a modest 2PA cross section for AM‐1′ . [2a], , …”
Section: Resultsmentioning
confidence: 99%
“…[8b] Because of the twisted molecular structure and lower conjugation efficiency related to the intermolecular charge transfer interactions, it was reasonable to expect a modest 2PA cross section for AM‐1′ . [2a], , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation